Today's Librarian: Debating Harry Potter (Today's Librarian, 2000)
Article on staff debate concerning the coming Harry Potter book.
2 page article in Today's Librarian newsletter
Master list item #51
File location is in the Raton File Cabinet drawer 3
Keywords: Wright, Thayla -- Librarian -- Raton, New Mexico; Harry Potter Debate -- Arthur Johnson Memorial Library -- Raton, New Mexico